Exposure to wood smoke particles leads to inflammation, disrupted proliferation and damage to cellular structures in a human first trimester trophoblast cell line. (September 2020) - Erlandsson, Lena; Lindgren, Robert; Nääv, Åsa; Krais, Annette M.; Strandberg, Bo; Lundh, Thomas; Boman, Christoffer; Isaxon, Christina; Hansson, Stefan R.; Malmqvist, Ebba
Abstract: The ongoing transition to renewable fuel sources has led to increased use of wood and other biomass fuels. The physiochemical characteristics of biomass combustion derived aerosols depends on appliances, fuel and operation procedures, and particles generated during incomplete combustion are linked to toxicity. Frequent indoor wood burning is related to severe health problems such as negative effects on airways and inflammation, as well as chronic hypoxia and pathological changes in placentas, adverse pregnancy outcome, preterm delivery and increased risk of preeclampsia. The presence of combustion-derived black carbon particles at both the maternal and fetal side of placentas suggests that particles can reach the fetus. Air pollution particles have also been shown to inhibit trophoblast migration and invasion, which are vital functions for the development of the placenta during the first trimester. In this study we exposed a placental first trimester trophoblast cell line to wood smoke particles emitted under Nominal Burn rate (NB) or High Burn rate (HB). The particles were visible inside exposed cells and localized to the mitochondria, causing ultrastructural changes in mitochondria and endoplasmic reticulum. Exposed cells showed decreased secretion of the pregnancy marker human chorionic gonadotropin, increased secretion of IL-6, disrupted membrane integrity, disrupted proliferation and contained specific polycyclic aromatic hydrocarbons (PAHs) from the particles. Taken together, these results suggest that wood smoke particles can enter trophoblasts and have detrimental effects early in pregnancy by disrupting critical trophoblast functions needed for normal placenta development and function. This could contribute to the underlying mechanisms leading to pregnancy complications such as miscarriage, premature birth, preeclampsia and/or fetal growth restriction. This study support the general recommendation that more efficient combustion technologies and burning practices should be adopted to reduce some of the toxicity generated during wood burning. Graphical abstract: Image 1 Highlights: Wood smoke particles were emitted under nominal- or high burn rate in a wood stove High burn rate emitted 3.5 times more PAHs than nominal burn rate Particles caused cytotoxicity & disrupted proliferation in exposed placenta cells Particles detected inside cells caused structural damage to mitochondria and ER LMW PAHs were detected at higher concentrations compared to HMW in exposed cells Abstract : CAPSULE: This study suggest that wood smoke particles can have detrimental effects early in pregnancy by disrupting critical trophoblast functions needed for normal placenta function.